The United States of Trump : how the president really sees America - O'Reilly, Bill (Henry Holt and Company, 2019)
O<U+2019>Reilly blends primary, never-before-released interview material with a history that recounts Trump<U+2019>s childhood and family and the factors from his life and career that forged the worldview that the president of the United States has taken to the White House. Not a partisan pro-Trump or anti-Trump book, this is an up-to-the-minute, intimate view of the man and his sphere of influence<U+2015>of “how Donald Trump<U+2019>s view of America was formed, and how it has changed since becoming the most powerful person in the world”<U+2015> from a writer who has known the president for thirty years. This is an unprecedented, gripping account of the life of a sitting president as he makes history.